Proximate composition, mineral and phytochemical constituents of Eleusine coracana (finger millet) - Bwai, Macham; Afolayan, Michael; Odukomaiya, Doyinsola; Abayomi, Orishadipe (International Journal of Advanced Chemistry, 2014)
The proximate composition, mineral and phytochemical constituents of Eleusine coracana (finger millets) was evaluated with the aim of providing data that will guide the effective utilization of it under exploited seed in food application. The proximate composition revealed the presence of moisture (6.99%), ash (2.37%), crude protein (10.28%), crude fibre (3.10%), crude lipid (0.83%) and carbohydrate (76.43%). The mineral composition revealed potassium (14.19 mg/g), sodium (6.86 mg/g), copper (0.10 mg/g), calcium (1.13 mg/g), magnesium (6.25 mg/g), zinc (0.22 mg/g), manganese (0.32 mg/g), Iron (0.11 mg/g), lead (0.001 mg/g) and Na/K 0.48. The phytochemical constituents present were tannins, steroids, phenols, alkaloids, terpenoids, cardiac glycosides and balsams. These results revealed that the seeds of Eleusine coracana (finger millet) contained essential nutrients which compete favourably well with those of other seeds in literature and it is suitable for health benefits and for use in herbal medicine to combat different diseases. Keywords: Eleusine Coracana, Finger Millet, Mineral Composition, Phytochemical, Proximate, Seed.